Assessment of a renewable energy system for Longyearbyen in 2030 - Innanen, Satu (2021)
To obtain the targets to halt global warming, a transition to renewable energy systems is crucial. Longyearbyen is an Arctic settlement on the Svalbard archipelago and currently Longyearbyen’s energy system is based on locally mined coal and imported diesel as a reserve source. The existing power plant is aging and there is uncertainty of how long the coal resources will last. Thus, new solutions for the energy system are needed. In this Bachelor’s thesis, a 100 % renewable energy system for Longyearbyen in 2030 is modelled with a modelling tool EnergyPLAN. In addition to the current system, two scenarios with different heat and electricity demands for the future system are modelled. In the 2030 scenario, 6.9 MW onshore wind, 16 MW offshore wind and 3.03 MW solar PV are needed. In the 2030 Lower demands scenario, the numbers are 10.35 MW, 8 MW and 7.49 MW, respectively. The results show that a renewable energy system for Longyearbyen is technically feasible. The costs of the renewable systems are higher than the current system, but investment and maintenance costs also stand for local jobs. In addition, if the costs of the CO2 emissions were included, the differences in the costs would be even smaller.